A community perspective of COVID-19 and obesity in children: Causes and consequences. (March 2021) - Tsenoli, Maido; Moverley Smith, Jane Elizabeth; Khan, Moien AB
Abstract: The pandemic of childhood obesity that has been increasing over the last decade has collided with the current pandemic of COVID-19. Enforced behavioural changes have resulted in a myriad of problems for children particularly in weight management. Restricted activity is the most obvious but many other aspects of life have exacerbated biological, psychosocial, and behavioral factors identified as risks for childhood obesity. Significant effort is required to turn around the prevailing tide of weight gain necessitating changes in personal and family behavior and diet, as well as high-level governmental and educational policy. Evidence-based, focused, long-term interventions which are adequately funded are required. Enthusiasm and optimism for change coupled with public engagement by utilization of new technology as well as traditional methods offers hope for change. Public health interventions in isolation are inadequate and bolder changes to central policies and social structure are needed for sustained change. This will allow some mitigation of the affects of COVID-19 but also reduce negative outcomes in future comparable situations. Highlights: The impact of COVID-19 on weight gain during the pandemic for children are significant. Weight management in children during and after the pandemic should be a priority. Biological, psychosocial, and behavioral factors associated with the development of childhood obesity have been magnified during the pandemic. Addressing these issues requires an integrated multi-faceted approach across all aspects of life.